Penurunan Kelelahan Pasien Diabetes Mellitus Tipe 2 dengan Relaksasi Otot Progresif - Mustafida, Ika; Rayasari, Fitrian; Fauziah, Munaya; Jumaiyah, Wati; Abriyanti, Rika Mustika (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of progressive muscle relaxation on fatigue in T2DM. This research used a quasi-experimental design with a pretest-posttest control group and a purposive sampling technique. According to the inclusion and exclusion criteria, 78 T2DM patients in the Cempaka Putih sub-district health center area, Central Jakarta, participated in this study. The results of this study showed that the average fatigue score in the intervention group decreased significantly (7.46) compared to the control group (1.77). A significant difference was between moderate fatigue in the intervention and control groups (p-value = 0.018). At the end of the study, it was found that DM complications were the most dominant variable influencing fatigue (Exp. B = 9.20). In conclusion, Progressive Muscle Relaxation has been proven to reduce fatigue scores in Type 2 Diabetes Mellitus, where the DM complication variable is the most dominant variable influencing the fatigue score of Diabetics. Keywords: Diabetes Mellitus Type 2, Fatigue, Progressive Muscle Relaxation